(untitled) (Atlas Journal of Biology, 2017)
The existence of evolutionarily degenerate biological structures (EDBS) is a major concept in biology. Biologists have often used the terms “vestige,” “rudiment,” and their adjective forms “vestigial” and “rudimentary” for EDBS since the nineteenth century. Some authors have advocated stricter usage of the terms than others have. For example, some have advocated restriction of the term “rudimentary” to embryonic structures, whereas others have also applied it to postembryonic EDBS. Likewise, some have restricted the term “vestigial” to putatively functionless structures, whereas others have applied it to structures that retain some function. Here, I sought to determine whether a consensus has been reached in the usage of such terms for EDBS. A sample of 200 articles in primary scientific literature from the twentieth and twenty-first centuries shows that through both centuries it has been more common to call EDBS “rudimentary” than to restrict the term “rudimentary” to embryonic structures, and it has been more common to attribute function or possible function to structures called “vestigial” than to restrict the term “vestigial” to putatively functionless structures. The consensus in both centuries has been less-strict usage of such terms; such usage is, in several ways, more logical than strict usage.